2014
DOI: 10.5194/isprsarchives-xl-8-1027-2014
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Coherence of winds and waves over the Arabian Sea and Bay of Bengal and their evolution during SW Monsoon: a novel application of along-track Radar Altimeter measurements from Space

Abstract: ABSTRACT:We have examined, for the first time, the spatial coherence of oceanic parameters, namely, the ocean surface wind and significant wave height (SWH), using near-instantaneous along-track sampling over vast oceanic tracks provided by Poseidon-2 Radar Altimeter onboard Jason-1. The spatial coherence length scales over the Arabian Sea and the Bay of Bengal regions, derived using Auto correlation analysis, display interesting characteristics in relation to onset and evolution of SW Monsoon over India. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…These higher values are particularly due to rain cells and so‐called sigma‐0 bloom patches in the ITCZ [ Dibarboure et al ., ]. The northern Indian Ocean shows low values of 1 Hz SSH error level except during the rainy season of the summer Monsoon [ Bhandari and Hareef Baba Shaeb , ] when the error level reaches 3 cm rms.…”
Section: Global Maps Of Altimeter Ssh Error Levelmentioning
confidence: 99%
“…These higher values are particularly due to rain cells and so‐called sigma‐0 bloom patches in the ITCZ [ Dibarboure et al ., ]. The northern Indian Ocean shows low values of 1 Hz SSH error level except during the rainy season of the summer Monsoon [ Bhandari and Hareef Baba Shaeb , ] when the error level reaches 3 cm rms.…”
Section: Global Maps Of Altimeter Ssh Error Levelmentioning
confidence: 99%
“…Due to the limitation of data available, the dynamic features between WS and Hs in the spatial domain are rarely reported in literature. Bhandari and Shaeb (2014) examined the spatial coherence of WS and Hs over the Arabian Sea with auto‐correlation functions. They found that the spatial coherence scales are of the order of 100–500 km.…”
Section: Discussionmentioning
confidence: 99%